Psychological features of implementation of social and communicational language - Kuznetsova, O. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article examines the psychological features of the implementation of socially communicative language intentions at non-specialized faculties, the mechanisms of speech formation from the standpoint of an active approach. The article revealed the essence of communicative competence by distinguishing the basic principles of communicative linguistics: the interaction of linguistic and social sides of communication; presence of the purpose, object, place and time of the specific cue in the linguistic intention of the person; training in foreign languages, based on the analysis of functions and conditions of communication, and then – on the identification of systematic features. There is an important role of the presence of linguistic intentions in the communicative competence, the ability to implement them in the process of communication and mastering a variety of linguistic formulas. Analyzing the subject of the study, we have identified some specific characteristics of foreign language as an academic discipline: the inability of foreign language to give a person direct knowledge of the reality; meaninglessness of foreign language, its infinity, dimensionlessness and homogeneity; the opportunity to realize the social and communicative needs of the subject of learning in the course of language activities and learning a foreign language. The subject of the article's analysis was also the differentiation and disclosure of the concepts of "speech", "language" and "speech activity" in terms of the active approach, in comparison with the linguistic concept of language, which is customary to be used in the methodology of teaching foreign languages. Thus language was considered as a mean, and speech – as a way of formulating thought in linguistic activity process of the subject of communication. It was concluded that linguistic means, on one hand, are the subjects of training, means and methods in process of activity are inseparable interconnection and interaction, and on the other hand – knowledge of the linguistic means is not the only condition for successful and effective mastery way of forming and formulating an opinion adopted in a foreign language environment.
Keywords: linguistic intention; educational and cognitive needs; psychological concept of formation of the individual's linguistic activity; dynamics of thinking in connection with speech; psychological view on methodological problems; generation of speech utterance